FEASIBILITY STUDY OF CONVERSION OF COAL INTO SYNFUEL - et al., Dr.V.PALVANNAN (International Journal of Advanced Science and Technology, 2019)
India is the third largest consumer of crude oil in the world, after the United States and China. India accounted 4.8% of total world oil consumption in 2016-17. The estimated total consumption of crude oil in India rose from 156.1 million  tons in 2007-08 to 245.4 million  tons in 2016-17 . Petroleum oil consumption in India is ever increasing at an average  rate of 8% per annum  in the past five years.